2014
DOI: 10.3126/njog.v7i2.11133
|View full text |Cite
|
Sign up to set email alerts
|

Use of Misoprostol in the Management of Early Pregnancy Loss

Abstract: aims:To evaluate the effectiveness of Misoprostol administered vaginally to assist complete evacuation in early pregnancy losses (incomplete abortion, missed abortion and blighted ovum). Methods:It is a descriptive study conducted in the Department of Ob/Gyn and Emergency Department Tribhuvan University Teaching hospital. All women with clinical/USG diagnosis of incomplete abortion, missed abortion and blighted ovum ≤12 weeks POG either from last menstrual period (LMP) or USG were inserted tab. misoprostol 800… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(20 reference statements)
0
2
0
1
Order By: Relevance
“…In another study similar results were reported with the success rate of 100% in 6 weeks or less, 86.3% in 7 to 9 weeks and 87% in 10 to 12 weeks. 13 Tang et al 14 reported the commonest side effect of Misoprostol to be diarrhea.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study similar results were reported with the success rate of 100% in 6 weeks or less, 86.3% in 7 to 9 weeks and 87% in 10 to 12 weeks. 13 Tang et al 14 reported the commonest side effect of Misoprostol to be diarrhea.…”
Section: Resultsmentioning
confidence: 99%
“…13 One case of anaemia with prolonged bleeding came to hospital only on the 17 th day with heavy bleeding and required three pints of blood transfusion and there were three cases of surgical evacuation done within 24 hours due to excessive bleeding (Table 3). So the medical evacuation should be used in selected cases whostay close to health facility with proper set up, where emergency surgical evacuation can be done specially for those cases with higher gestation.…”
Section: Resultsmentioning
confidence: 99%
“…Misoprostol juga diberikan pada beberapa kasus Abortion Incomplete karena telah terdapat bukti efektif, aman dan dapat diterima bagi pasien yang tidak memungkinkan dilakukan pembedahan atau menghindari prosedur invasif [32]. Pada kasus missed abortion hanya ditemukan 1 pemberian di RS X. Walaupun sedikit, penggunaan off-label Misoprostol pada indikasi ini memiliki keberhasilan yang paling tinggi diantara kasus aborsi lainnya [33]. Selain itu, penanganan menggunakan obat juga dinilai lebih berhasil daripada penanganan secara natural pada kasus keguguran pada trimester pertama [32,34].…”
Section: Blighted Ovum 5 (14%) -unclassified